(3TQM GdCRgQjI aj Yde GdYQHjIs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO,J (B905 (3g` s ((3CYQGHj eMeO CMeO YHOGdLhGO CMeO GdaQThWj GdUYjOj GdTGaYj s)
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY GdCMhGd ajbhd GdYHO hdG jSYfj eNGdaJg Cf CTQM ebOeJj GdCRgQjI aj Yde GdYQHjI GdJj CedjJgG dHYV GdWdHI s
(3BNQgG (B:s
(3ef GdLfI LGQ heLQhQ eJYdb CjVkG HjhShS, hGdfGS eYWha Ydi GdLfI haj gPG GdbOQ caGjI ddeHJOF GdMeO ddg Je gPG GdTQM s
(3GdfSNI HgG MhGTs
(3GfJgi ef JCdja GdTQM Sf`(B902(3`Is
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs